Mortalidade dos hipertensos vinculados à estratégia saúde da família em João Pessoa: um estudo de coorte - Silva, Clarice César Marinho (2019)
The cohort of hypertensive adults enrolled in Basic Care in the city of João Pessoa, started in 2009 with waves in 2010, 2011 and 2016 is the only active cohort in Brazil. Considering the importance of assessing the satisfaction and follow up of users with the services provided by Primary Care for the evaluation of health programs, this study had, as main objective, to analyze the characteristics of the hypertensives enrolled in Primary Care who died during the period of the study of the a cohort of hypertensive adults in the city of João Pessoa-PB, from 2009 to 2016. This is a retrospective cohort based on an initial sample of 343 hypertensive patients enrolled in Hiperdia, culminating in 2016, with 34 deaths. The verbal autopsy questionnaire was applied to the relatives of the deceased hypertensives. Imputation of the missing data on the characteristics of hypertensive individuals was performed by the Hot Deck method and the final sample was validated using the Bootstrap resampling method. In order to evaluate the degree of satisfaction and the follow-up of hypertensive patients alive and deceased during the cohort period, a questionnaire validated since the first wave was used. In the sample of hypertensive women in the sample in 2016, both the living and the deceased preponderated the female gender, aged equal to or above 60 years, brown, with less than nine years of study, who lived with someone, had an income higher than a minimum wage and were considered economically non-active. There was no significant difference between the means of arterial pressures between the living and deceased groups, both with high blood pressure levels. The groups were considered mostly unaccompanied, and there was no significant difference (5%) between the type of follow-up and the pressure control. There was a significant difference (5%) between the satisfaction scores between the groups, of which the living were less satisfied than the deceased. These had more associated diseases. Through the verbal autopsy, it was observed that, from the perspective of the caregivers, the assistance to the hypertensive patient proved to be inadequate in several levels of attention regarding the process of the disease until its outcome culminated with the death. It was concluded that, in addition to the significant loss of follow-up of hypertensive cohorts, in the Primary Care of the Ministry of Health, the care with the hypertensive in the county of João Pessoa, were insufficient with an inadequate adherence to the treatment, presenting risk factors such as associated diseases and complications related to hypertension, which may have triggered early deaths.